Special topics in calamity physics - Pessl, Marisha (London Penguin Books, 2007)
A darkly funny coming-of-age novel and a richly plotted suspense tale told through the distinctive voice of its heroine, Blue van Meer. After a childhood moving from one academic outpost to another with her father (a man prone to aphorisms and meteoric affairs), Blue is clever, deadpan, and possessed of a vast lexicon of literary, political, philosophical, and scientific knowledge--and is quite the cineaste to boot. In her final year of high school at the e?lite (and unusual) St. Gallway School in Stockton, North Carolina, Blue falls in with a charismatic group of friends and their captivating teacher, Hannah Schneider. But when the drowning of one of Hannah's friends and the shocking death of Hannah herself lead to a confluence of mysteries, Blue is left to make sense of it all with only her gimlet-eyed instincts and cultural references to guide--or misguide--her.--From publisher description.
Keywords: Young women -- Fiction